1974
DOI: 10.1111/j.1348-0421.1974.tb00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium on the Cell Infectivity of Virulent Shigella flexneri 2a

Abstract: Effect of calcium ions (Ca++) on the virulence of Shigellaflexneri 2a was examined with reference to its infectivity to cultured cells, the guinea pig eye, and the ligated small intestine of rabbits. The organism grown in a calcium-containing medium showed a significantly higher ability to penetrate HeLa cells than that of organism grown in a calcium-deficient medium. This ability was constantly maintained in the presence of Ca++, while readily lost in the absence of Ca++. Similarly, its pathogenicity for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
1

Year Published

1975
1975
1988
1988

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…In this connection, we have observed that a virulent strain of S. flexneri 2a maintained its high infectivity to HeLa cells in culture when grown in a calcium-containing medium, but it readily lost the ability when grown in a calcium-deficient medium [24]. Here, we present an observation on the effect of other metallic cations on the virulence of S. flexneri 2a with reference to the infectivity to HeLa cells and the guinea pig eye.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…In this connection, we have observed that a virulent strain of S. flexneri 2a maintained its high infectivity to HeLa cells in culture when grown in a calcium-containing medium, but it readily lost the ability when grown in a calcium-deficient medium [24]. Here, we present an observation on the effect of other metallic cations on the virulence of S. flexneri 2a with reference to the infectivity to HeLa cells and the guinea pig eye.…”
mentioning
confidence: 86%
“…The bacterium used in this study was S. flexneri 2a, strain 5503 maintained in the lyophilized state, and subcultured in Luria broth [24] at 37 C for 18 hr. One tenth milliliter of the broth culture was then inoculated on Luria agar (LA) [24] supplemented with CaCl2, MgCl2, MgSO4, FeSO4, CoCl2, CdSO4, MnCl2, and 5ZnO 2CO3 at a final concentration of 5 mm and incubated at 37 C for 18 hr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One milliliter of 10-fold dilution of the bacterial suspension in Eagle's MEM (Nissui Seiyaku Co., Ltd., Tokyo) supplemented with each preparation and 10% normal calf serum were poured into the Lab-Tek Tissue Culture Chamber/Slide (Lab-Tek Products Inc., Ill., U.S.A.) loaded with HeLa cell monolayer and incubated overnight at 37 C under 5% CO2-95% air in a humidified incubator. Enumeration of the cells containing the organisms and calculation of phagocytosis rate were performed in the same way as that employed in the cellinfection system (15,16).…”
mentioning
confidence: 99%
“…Preparation of the cells (monolayered culture of HeLa S3 cells) and infection with the bacilli were performed by the same method as reported previously (15). The organisms used as inoculum were cultivated on Luria agar medium (16) supplemented with or without MgSO4. In the experiment of phagocytosis of HeLa cells, strain 5503 cultivated on the agar medium with MgSO4 (LA+) was killed by autoclaving at 121 C for 15 min or by treatment with 0.1 % formalin at 37 C for 48 hr.…”
mentioning
confidence: 99%